Controlled residual surface contamination of gamma-TiAl, induction melted in ceramic crucibles - Barbosa, J. (2001)
This paper describes the melting procedure of gamma TiAl, using a multi-layered refractory crucible based on stabilized zirconia. Hardness and residual element contamination will be presented and discussed for samples let solidified and cooled inside the crucible in order to simulate the worst cooling conditions, regarding metal-mould reaction (samples subjected to the longest cooling time experimentally available). Results will be compared with samples melted and solidified in calcia and single stabilized zirconia crucibles. Some microhardness, residual contamination profiles and surface finish of samples poured into different refractory investment casting moulds will also be presented and discussed.